Pengaruh Kepatuhan Pada Regulasi, Pemanfaatan Teknologi Informasi, dan Komitmen Pimpinan Terhadap Pengelolaan Aset Tetap oleh Badan Pendapatan dan Aset Daerah Provinsi Nusa Tenggara Timur - Soro, Crispim Pereira Leo; Sonbay, Yolinda Yanti; Bibiana, Rere Paulina; Perseveranda, M. E.; Adrianus, Jou Sewa (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the significant influence of compliance with regulations, simultaneous use of information technology, and leadership commitment to fixed asset management in the East Nusa Tenggara (NTT) Provincial Government. A quantitative approach was used in this research. Based on inferential analysis, fixed asset management is significantly influenced by leadership commitment, use of information technology, and compliance with regulations, at least in part. Meanwhile, simultaneously it shows that leadership commitment, use of information technology, and compliance with regulations have a positive and significant influence of 73.1% on fixed asset management. East Nusa Tenggara Province Regional Revenue and Assets Agency.